More female manager hires through more female managers? Evidence from Germany - Thorsten Schank; Mario Bossler; Alexander Mosthaf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Women are heavily underrepresented in management positions. This paper investigates if there is state dependence in the share of female manager hires in German plants to assess if increased female representation in management positions is sustainable. Using administrative data from the Integrated Employment Biographies of the IAB, we apply dynamic tobit models and dynamic linear models taking unobserved heterogeneity and the endogeneity of lagged dependent variables into account. We find that there is state dependence in the female share of manager hires. Dynamic linear models for the number of female manager hires also point to the sustainability of female manager hires showing that there is state dependence in the number of female manager hires. However, there is no state dependence in the number of male manager hires.
Keywords: C23; M12; J16; 330